ANALYSIS EFFECTIVENESS CONVENIENCE USE PAYMENT TRANSACTION NON- CASH FINANCE TO USE OF QRIS - isra Hayati; Amelia Rizky (CERED Indonesia Institute, 2023)
Objective study This For know effectiveness convenience use payment transaction cashless finance _ to QRIS use . Problems in study This is Still there are students of the Sharia Business Management Study Program at the Faculty of Islamic Religion UMSU who do not know or use QRIS Bank Syariah. Approach research used _ in study This use approach quantitative . Study This use method Data analysis techniques using data quality tests , validity tests , reliability tests , assumption tests classic , normality test , heteroscedasticity test , autocorrelation test , regression test simple , hypothesis test , partial test t count (t test), test of determination , with amount sample as many as 32 determined respondents with non-probability sampling technique . Method data collection used is questionnaire .Research results show effectiveness convenience use payment transaction cashless finance _ influential to utilization QRIS use . this _ proven with he refused hypothesis H0 through testing hypothesis Where there is t count value (26.547) > t table (1.69389), with a sig value of 0.000 <0.05 indicates H0 is rejected and Ha is accepted . Based on the Determination test An R Square value of 0.879 or 87.9% indicates about 87.9% variable The use of the Indonesian Standard Quick Response Code (Y) is influenced by convenience use payment transaction non- cash finance ( X). Temporary the rest 12.1 % is influenced by variables that are not researched in study this .